1988
DOI: 10.1007/bf00917897
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of interleukin-2 and ?-interferon productionin vitro on cord blood lymphocytes andin vivo on primary cellular immunodeficiency patients with thymic extract (Thymostimulin)

Abstract: Cord blood mononuclear cells (MNC) were isolated from 20 normal full-term newborns. These MNC were preincubated with either 50, 100, or 200 micrograms/ml Thymostimulin or without Thymostimulin. The interleukin-2 (IL-2) and gamma-interferon (gamma-IFN) production, cytotoxicity, and lymphoproliferation and IL-2 receptor (Tac) expression were all significantly increased after Thymostimulin treatment. For evaluation of the in vivo effect, two combined-immunodeficiency patients defective on the thymic level, one wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

1989
1989
1997
1997

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 22 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…10gg/ml phytohaemagglutinin (PHA)) was used to stimulate the patient's MNC in order to measure IL-2 production [12,13]. Supernatants were also taken from the MNC culture stimulated with PHA for 3 days.…”
Section: Me~o~mentioning
confidence: 99%
See 2 more Smart Citations
“…10gg/ml phytohaemagglutinin (PHA)) was used to stimulate the patient's MNC in order to measure IL-2 production [12,13]. Supernatants were also taken from the MNC culture stimulated with PHA for 3 days.…”
Section: Me~o~mentioning
confidence: 99%
“…The levels of IFN-r in the culture supernatant and in the serum were either measured by an ELISA method (HBT Human, Interferon Gamma ELISA Test Kit D03M and D03S respectively, CA Leiden, Netherlands) or by bioassay. Bioassay was performed using the cytopathic effect manifested by amniotic cells (WISH cells) after infection with Sindbis virus [12]. Briefly, the culture supernatants were obtained from the patient's MNC after stimulation with PHA (10 gg/ml) for 3 days.…”
Section: Me~o~mentioning
confidence: 99%
See 1 more Smart Citation
“…Mass.). IFN-y assays of the supernatant were made using the cytopathic effect manifested by amniotic cells (WISH cells) after in fection with Sindbis virus [15]. Briefly, the culture supernatants were obtained from the patient's MNC after stimulation with PHA (10 pg/ml) for 3 days.…”
Section: Methodsmentioning
confidence: 99%
“…kargcr.ch known to help restore immune function. Experimental and clinical studies have shown that thymostimulin is a safe and potent immunomodulatory agent, capable of re storing T-cell function in immunocompromised hosts [4][5][6][7], Thymostimulin has been successfully employed in the therapy of both primary and secondary immunodeficien cies [8][9][10], Recent studies support the usefulness of an immunomodulating approach to COPD treatment [11][12][13]. A reduction of the frequency and/or severity of infec tious events.…”
Section: Introductionmentioning
confidence: 99%